Application of Edible Coating from Beneng Taro Starch, Chitosan and Ginger Essential Oil to Maintain the Quality of Mango: Aplikasi Pelapis Edibel dari Pati Talas Beneng, Kitosan dan Minyak Atsiri Jahe untuk Mempertahankan Kualitas Mangga - Meindrawan, Bayu; Kusuma, Azahra Wibi; Yuniarti, Rahma; Nabila, Firyal Giani; Rahmayanti, Diana; Pamela, Vega Yoesepa (jurnal makanan tropis dan teknologi agroindustri, 2024)
Mango fruits are a popular Indonesian export commodity. Still, they could not penetrate several international markets because they have a short shelf life and are easily damaged, especially during transportation and distribution. Edible coating can be an alternative to extend the shelf life of mangoes. Edible coatings are formulated from beneng taro starch combined with chitosan and ginger essential oil (0; 0.5; 1 and 2% v /v). The research results showed that the edible coating formulation of beneng taro starch, chitosan, and 2% ginger essential oil was the best formulation which gave the lowest final weight loss value (10.06 %), highest hardness (33.56 N), lowest carbon dioxide production (850,5 ppm/day), lowest pH (4.2), highest total dissolved solids (82°brix) compared to other formulations. The visual appearance of mangoes with the edible coating application did not change significantly compared to mangoes without the edible coating. In conclusion, the application of beneng taro starch, chitosan, and essential oil edible coatings maintained the quality of mangoes during storage.